1997
DOI: 10.1099/0022-1317-78-10-2575
|View full text |Cite
|
Sign up to set email alerts
|

Spliced human endogenous retroviral HERV-H env transcripts in T-cell leukaemia cell lines and normal leukocytes: alternative splicing pattern of HERV-H transcripts.

Abstract: The majority of human endogenous retroviral HERV-H elements in the human genome have large deletions in pol and lack most of env, 5-10 % are more or less complete with a potentially immunosuppressive transmembrane protein-encoding env region. Spliced HERV-H env transcripts were detected in T-cell leukaemia cell lines and lymphocytes from healthy blood donors by using RT-PCR. The transcripts all contained a splice donor in the leader region downstream from the primer-binding site and a previously unreported spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
(38 reference statements)
1
22
2
1
Order By: Relevance
“…Additionally, we observed upregulation of nonfunctional transcripts derived from mariner 2 transposon (HSMAR2) remnants and human endogenous retrovirus H (HERV-H) sequences that have acquired premature termination codons (PTCs) during evolution. Previous studies [15][16][17] and our analyses of expressed-sequence tags showed that at least some HSMAR2 and HERV-H transcripts undergo splicing. Accordingly, we observed B1.0-kb transcripts corresponding to the size of the spliced HERV-H message (Fig.…”
Section: E T T E R Smentioning
confidence: 62%
“…Additionally, we observed upregulation of nonfunctional transcripts derived from mariner 2 transposon (HSMAR2) remnants and human endogenous retrovirus H (HERV-H) sequences that have acquired premature termination codons (PTCs) during evolution. Previous studies [15][16][17] and our analyses of expressed-sequence tags showed that at least some HSMAR2 and HERV-H transcripts undergo splicing. Accordingly, we observed B1.0-kb transcripts corresponding to the size of the spliced HERV-H message (Fig.…”
Section: E T T E R Smentioning
confidence: 62%
“…Further, polymorphism and epigenetic events such as imprinting could lead to both inter-and intraindividual variation in HERV expression. An interindividual variation in RNA expression has been shown for several HERVs (7,42,48,85).…”
Section: Discussionmentioning
confidence: 99%
“…The annotated genes are distributed among the SDs on chromosomes 2, 3, 7, 10, 11, and 13. The described functions of the non-OR genes vary widely and include a hypothetical zinc finger gene, an oxytocin receptor, a HERV-H protein, and an A-kinase anchoring protein (AKAP)-binding sperm roporin (Kimura et al 1992;Lindeskog and Blomberg 1997;Carr et al 2001). PC3-96, an autophagy-like protein, is the only non-OR gene that lies within 50 kb of a 7E gene (∼9 kb 5Ј of the 7E gene at 3.125919193).…”
Section: Org Downloaded Frommentioning
confidence: 99%